2019
DOI: 10.1080/20477724.2019.1678939
|View full text |Cite
|
Sign up to set email alerts
|

Arboviruses in the East African Community partner states: a review of medically important mosquito-borne Arboviruses

Abstract: Mosquito-borne diseases, including arbovirus-related diseases, make up a large proportion of infectious disease cases worldwide, causing a serious global public health burden with over 700,000 deaths annually. Mosquito-borne arbovirus outbreaks can range from global to regional. In the East African Community (EAC) region, these viruses have caused a series of emerging and reemerging infectious disease outbreaks. Member states in the EAC share a lot in common including regional trade and transport, some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 215 publications
(324 reference statements)
0
35
0
Order By: Relevance
“…Mosquitoes are known to act as reservoirs of extensive pathogens ( Xia et al, 2018 ; Nyaruaba et al, 2019 ), several mosquito-borne viruses (arboviruses) causing human diseases remain the global public health concerns ( Tandina et al, 2018 ). However, with the constant evolution and crossing species barrier, the emergence of novel zoonotic pathogens is one of the greatest challenges to global health security ( Borland et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes are known to act as reservoirs of extensive pathogens ( Xia et al, 2018 ; Nyaruaba et al, 2019 ), several mosquito-borne viruses (arboviruses) causing human diseases remain the global public health concerns ( Tandina et al, 2018 ). However, with the constant evolution and crossing species barrier, the emergence of novel zoonotic pathogens is one of the greatest challenges to global health security ( Borland et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the relationships between nature, human activities, and climate are As a result of the increased anthropogenic activities, livestock movement, urbanization, and predicted climate change, there is a real risk that these factors might jointly enable the spread of RVF in East Africa. East Africa continues to be an endemic region for RVF, and the ongoing trade partnerships (38) could lead to the introduction of the virus to new non-endemic regions, e.g., in Uganda and Burundi. Therefore, it is vital to assess its effect on RVF distribution and spread to successive suitable areas to help design timely mitigation measures and decrease the negative impacts of future climate change.…”
Section: Discussionmentioning
confidence: 99%
“…With travel and trade thought to be major drivers of emerging pathogen spread (Kilpatrick, 2012), the movement of livestock and people among East African countries could enhance the circulation of emerging pathogens, especially given that high arboviral activity has been reported across the region (Mossel et al, 2017;Nyaruaba et al, 2019). Smallholder livestock production in East Africa is associated with livestock movement across provincial and national borders to livestock markets (LMs) in peri-urban areas (Fèvre et al, 2005) in which animals have been found to be heavily infested by ticks (Sang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of CCHF (Dunster et al, 2002) and RVF (WHO, 2018) have been reported before in Western Kenya, and there is serological evidence of circulation of chikungunya, yellow fever, West Nile, and RVF viruses (Cook et al, 2017;Inziani et al, 2020;Mease et al, 2011;Nyaruaba et al, 2019). While reports on the occurrence of zoonotic vector-borne bacteria are scant, the high prevalence of malaria in Western Kenya results in under-investigation of other causes of febrile illnesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation